Impact of COVID-19 pandemic on child poisonings: A retrospective study at a Greek children's hospital - Elisabeth Kotsi; Gerasimos Panagiotis Milas; Marina Thanasia; Konstantinos Papantzimas; Stavroula Kostaridou (Elsevier, 2024)
Objectives: Unintentional child poisoning is a significant health issue worldwide, and while most cases are not severely toxic, some require specific medical interventions.The aim of this study is to examine thecorrelation between the lockdown following the COVID-19 pandemic and the incidence of acute child poisoning. Methods: To better understand the problem, we conducted a retrospective study of 103 children examined from 2019 to 2021 at the Penteli Children's General Hospital. Results: The findings revealed that drugs (37.9 %) and cigarettes (32.0 %) were the most common poisons, followed by detergents (5.9 %) and insecticides (4.9 %). Interestingly, the number of poisoned children increased significantly in 2020 (N = 46) compared to 2019 (N = 25). Most of the cases occurred during the COVID-19 lockdown, accounting for 44.7 % of all cases. Conclusion: In conclusion, pediatric poisoning remains a global emergency and should be prevented through proper storage and adult supervision of chemicals to avoid accidents.